Relationship Between Knowledge Level and Compliance in Tuberculosis Patients - Erni Anika Sari; Kumala Sari PDW; Defi Rafika (Indonesian Journal of Pharmaceutical Education, 2023)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis which mostly attacks other organs of the body. The source of transmission is TB patients, especially patients who contain TB germs in their sputum. Someone who has high knowledge has also high awereness of health and high motivation to recover. In the treatmnet of tuberculosis succes depends on the support of the family and the knowledge of the patient. If treatment is not complete, it can lead to the emergence of drug- resistant tuberculosis bacteria. If this happens, the germs will spread and control efforts will be more difficult. Purpose: The purpose of this study was to determine whether there was a relationship between the level of knowledge and adherence to the treatment of pulmonary tuberculosis patients. This study uses a analcyticcal sucrvey design with a cross sectional approach with data collection using a questionnaire to respondents of pulmonary tuberculosis patients who meet the inclusion criteria. The data obtained were collected and analyzed using the SPSS program. The results of the chi-square analysis showed 0.05%, 0.036, which means that there is a significant relationship between the level of knowledge and adherence to the treatment of pulmonary tuberculosis patients.